Health and Culinary Art in Antiquity and Early Byzantium in the Light of "De re Coquinaria" - Kokoszko, Maciej; Rzeźnicka, Zofia; Jagusiak, Krzysztof (Studia Ceranea, 2012)
The article is aimed at indicating and analyzing connections existing between De re coquinaria and medicine. It is mostly based on the resources of extant Greek medical treatises written up to the 7th century A.D. As such it refers to the heritage of the Corpus Hippocraticum, Dioscurides, Galen, Oribasius, Anthimus, Aetius of Amida, Paul of Aegina, to name but the most important. The authors of the study have tried to single out from De re coquinaria those recipes which have the tightest connections with medicine. They are: a digestive called oxyporum, two varieties of dressings based on fish sauce, i.e. oxygarum digestibile and oenogarum, herbal salts (sales conditi), spiced wine (conditum paradoxum), honeyed wine (conditum melizomum viatorum), absinthe (absintium Romanum), rosehip wine (rosatum), a soup (or relish) pulmentarium, a pearl barley-based soup termed tisana vel sucus or tisana barrica, an finally nettles. In order to draw their conclusions, the authors of the article projected the data from De re coquinaria upon a wide background of extant information retrieved from medical writings. The conclusions demonstrate that those who contributed to the present form of De re coquinaria, even if they did not possess strictly medical expertise, remained under a heavy influence of Hippocratic and Galenic teachings. As a result, De re coquinaria should be seen as yet another work of antiquity that supports the existence of an indissoluble bond between medical doctrines and culinary practice of the times.